2012
DOI: 10.1108/13522751211191973
|View full text |Cite
|
Sign up to set email alerts
|

Why we ignore social networking advertising

Abstract: PurposeThe purpose of this paper is to focus on college students, users of online social networks, as main sources of information that helps advertisers understand the ways in which advertisements are perceived online.Design/methodology/approachResults were reached through qualitative research. Personal in‐depth interviews, utilizing Zaltman Metaphor Elicitation Technique (ZMET), were conducted among 20 college students. Interviews consisted of using screenshots of advertisements in online social networks to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…On the other hand, the study of Hadija, Barnes, and Hair (2012) found that the users of online social networks do not dislike advertisements, but just simply do not notice them. Other content found in online social networks mitigates the attractiveness of the advertisements.…”
Section: Study Advertising and Public Relation Factors Affecting Audimentioning
confidence: 99%
“…On the other hand, the study of Hadija, Barnes, and Hair (2012) found that the users of online social networks do not dislike advertisements, but just simply do not notice them. Other content found in online social networks mitigates the attractiveness of the advertisements.…”
Section: Study Advertising and Public Relation Factors Affecting Audimentioning
confidence: 99%
“…Maxwell (2013) reported that online shoppers displayed positive cognitive responses towards brand SNS, but had unfavorable conative attitudes. Hadija et al (2012) determined little cognition (cognitive response) and indifferent affective attitudes towards social media advertising among 20 college students in the US. Kumar et al (2013) ascertained that WOM on SNS resulted in the rise of cognitive and behavioral responses towards brands when consumers with a large influence disseminate the marketing content among their social network of friends.…”
Section: Im Advertising Effect On Teenager Attitudesmentioning
confidence: 99%
“…Nielsen and Vizu [42] reported that marketers planned to continue to increase (63 %) their online advertising expenditure in 2013 in order to create direct responses and to establish brand awareness. Conversely, Hadija et al [30] concluded that social network users did notice the advertising, but focused on the content, such as the newsfeed and friends' profiles. Although several of the advertisements on the SNS did catch their attention owing to design, color, tagline and so forth, these were quickly overlooked in favor of more stimulating content; however, this was only a small qualitative study that included twenty respondents.…”
Section: Key Findingsmentioning
confidence: 99%
“…A number of studies have identified Generation Y as the main users of online digital and online technological gadgets and innovations such as SNS and mobile applications and, consequently, a target market for online marketers [16,30,38,49,61]. Furthermore, several studies have revealed that students are the primary users of SNS [32,51,52,57], and are hence exposed to advertising on SNS such as Facebook.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation